Infectious Myelitis - Asundi, Archana; Cervantes-Arslanian, Anna M.; Lin, Nina H.; Barbosa, Felipe (Seminars in Neurology, 2019)
Myelitis refers to inflammation of the spinal cord which can result in a spectrum of neurologic impairment. Infectious pathogens are an important etiologic category, and can result in myelitis through direct pathogenic effect or through immune-mediated parainfection; this review focuses on the former category. The spectrum of clinical manifestations is summarized and a diagnostic workup provided to aid clinicians in developing an approach to patients presenting with symptoms suggestive of infectious myelitis. This is followed by an overview of the important viral, bacterial, parasitic, and fungal causes of infectious myelitis. The typical presentations, diagnostic modalities, and treatment approaches are outlined for key pathogens culprit in infectious myelitis to allow clinicians to promptly recognize and diagnose specific infectious etiologies of myelitis.
Keywords: infection; myelitis; myelopathy